Classroom discourse in EFL teaching. - Strobelberger, Katrin (Diplomica Verlag, 2012)
Hauptbeschreibung This study analyses examples of classroom discourse, one of the most important influences on students' experience in schools, in EFL classes. The central idea of the author's enquiry is to compare classroom discourse in two secondary schools in two European countries, namely Austria on the one hand, and Spain on the other hand. The focus of the study is on EFL classes taught by a team of a non-native speaker teacher and a native speaker assistant. The purposes of this study are to gain insights into classroom communication, to compare classroom discourse in two different coun.